Provoking feminisms - Allen, Carolyn; Howard, Judith A. (The University of Chicago Press, 2000)
Un livre stimulant et incisif, Provoking Feminisms est une collection d'essais, de commentaires et de réponses sur certaines des questions les plus controversées de la théorie féministe d'aujourd'hui. Des conversations spécifiques sont centrées sur des sujets de débat tels que la théorie du point de vue féministe ; le genre comme catégorie analytique ; problèmes de "différence" sexuelle ; et la vie privée et les représentations du personnel. Chaque échange parle puissamment des enjeux actuels au cœur de l'érudition féministe et comprend des discussions à partir d'un échantillon de disciplines : théorie politique/sociale, philosophie, sociologie, études culturelles et théorie critique. Intense et rigoureux, Provoking Feminisms est un ouvrage crucial pour quiconque s'intéresse à l'état de l'érudition féministe contemporaine.
Keywords: anthologie; approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; point de vue situé; sciences humaines; thématiques; épistémologie

Experiments in knowing: Gender and method in the social sciences - Oakley, Ann (The New Press, 2000)
Ann Oakley came to widespread attention as part of the new school of British feminists to emerge in the 1960s, and has since earned a reputation as one of the most innovative feminist thinkers and social scientists writing today. In Experiments in Knowing, a major new work, Oakley integrates her personal and professional thinking to examine the historical development of methodology in the social and natural sciences, demonstrating how both fields have been subject to a process of "gendering." Oakley not only reconciles the long-standing opposition between the quantitative and the qualitative methods but shows that the experimental and intuitive approaches must be used in tandem to provide a full understanding of any subject of scientific inquiry. Written in accessible language, Experiments in Knowing addresses themes of common interest across such diverse fields as social policy, education, health, and women's studies. Certain to generate considerable debate, it is both a fascinating history of the practice of social science from a feminist perspective, as well as an argument for a new way of thinking about our ways of knowing.
Keywords: 1900-1999; approches et analyses; cours; discipline; europe; fem1000; genre; identités LGBTQIA2+; point de vue situé; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences; sciences humaines; sciences sociales; thématiques; théories féministes; épistémologie